2018
DOI: 10.1021/acs.jpcc.8b01698
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Ab Initio Study of Anhydrous Dehydrogenation of Linear-Chain Alcohols on Cu(110)

Abstract: The catalytic behavior of Cu surfaces in the anhydrous production of aldehydes from alcohols, a process of industrial significance, is puzzling: the two simplest alcohols (methanol and ethanol) show dramatically different decomposition behavior on Cu. Here, we study the thermodynamic and kinetic processes involved in the anhydrous dehydrogenation of linear-chain alcohols including methanol, ethanol, 1-propanol, and 1-butanol on the Cu(110) surface using multiscale approaches. First, we obtain the adsorption st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 70 publications
7
37
0
Order By: Relevance
“…In previous work the lowest energy structure for each alkoxide was determined. 6 These structures were confirmed to be stable/metastable by harmonic frequency analysis.…”
Section: Multiple Basins In the Energy Landscape Of Adsorptionmentioning
confidence: 81%
See 2 more Smart Citations
“…In previous work the lowest energy structure for each alkoxide was determined. 6 These structures were confirmed to be stable/metastable by harmonic frequency analysis.…”
Section: Multiple Basins In the Energy Landscape Of Adsorptionmentioning
confidence: 81%
“…The configurations of methoxy and ethoxy remain unchanged compared to those previously reported. 6 The newly discovered structures were more stable by 0.02 and 0.08 eV/molecule for 1-propoxy and 1-butoxy, respectively. Such energy stabilization is associated with the variation in the orientation of the molecule tail with respect to the β-C-O axis.…”
Section: Multiple Basins In the Energy Landscape Of Adsorptionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also based on DFT calculations, Krajčí et al demonstrated the CO/CO 2 selectivity of MSR on many alloys, e.g., PdZn, PtZn and NiZn [13]. Chen et al [14], Lausche et al [15], and Kramer et al [16] studied the selectivity of the dehydrogenation of methanol on Cu(110), Ni(100) and Ni(111), respectively. MSRs on Pt [16], Pd [16], Pt 3 Ni alloy [17], Pt-Skinned PtNi Bimetallic Clusters [18] and Co [19] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, experimental evidence for formaldehyde formation on copper catalysts through direct decomposition of methanol exists [2][3][4][5] , although the underlying pathways remain unclear. So far, theoretical calculations have only been able to deal with this reaction scheme on a static level using transition state theory [6][7][8][9][10][11][12] or a dynamical level but with a frozen surface 13 . However, these levels of theory exclude exchange of energy between the surface and the molecule and transition state theory excludes any dynamical effects such as steering as well.…”
Section: Introductionmentioning
confidence: 99%